Hyperopia reserve among 6‒8-year-old primary school students in Jing’an District， Shanghai - WANG Limeng; XU Wenyan; WANG Xiangdong; GUO Yawen; ZHOU Zhou; HE Xiangui (Shanghai yufang yixue)
ObjectiveTo understand the uncorrected visual acuity, spherical equivalent and hyperopia reserve of 6‒8-year-old primary school students in Jing’an District of Shanghai, and to provide a scientific basis for further myopia prevention and control.MethodsA total of 619 children aged between 6‒8 years old from three primary schools in Jing’an District were selected by cluster sampling method for uncorrected eye visual acuity examination and diopter examination after cycloplegia (mydriasis).ResultsThe mean uncorrected visual acuity of the 619 students aged 6‒8 years old was (4.9±0.2), and the mean spherical equivalent was (0.84±1.11) D. The difference in uncorrected visual acuity was not statistically significant as the age increased (F=0.057, P=0.812), but the spherical equivalent decreased with the increase of age, showing a statistically significant difference (F=26.533, P<0.001). There was no statistically significant difference in uncorrected visual acuity (t=-1.614, P=0.107) and spherical equivalent (t=-1.675, P=0.094) between students of different genders. Finally, among the 619 students, 59.80% of them had abnormal uncorrected visual acuity, 34.90% had insufficient hyperopia reserve, and only 5.30% had sufficient hyperopia reserve. Besides, the proportion of abnormal uncorrected visual acuity in 7-year-old students was 67.50%, higher than that of students with other ages, and the difference was statistically significant (χ2trend=29.729, P<0.001). While the difference in abnormal uncorrected visual acuity between students of different genders was not statistically significant (χ2=0.068, P=0.967).ConclusionThe deficiency of hyperopia reserve in 6‒8-year-old students in Jing’an District of Shanghai is serious. Attention should be paid to the visual acuity of school-aged children in lower grades, and intervention measures should be actively carried out to slow down the progression of myopia.